The Long-Term Impact of In-Utero Cigarette Taxes on Adult Prenatal Smoking - Lauren Hoehn-Velasco; Michael Pesko; Serena Phillips (Institute of Labor Economics (IZA), 2022)
This study examines the long-term link between in-utero cigarette taxes and adult prenatal smoking. We use U.S. birth certificate records to demonstrate that exposure to higher in-utero cigarette taxes (over 1965-2001) reduces later-life adult pre-pregnancy and prenatal smoking. We also show that higher in-utero cigarette taxes have long-lasting effects on adult health, and intergenerational consequences for infant health. Finally, we demonstrate that larger in-utero tax responsiveness correlates with smaller contemporary cigarette tax responsiveness, suggesting that higher in-utero taxes may alter the composition of remaining smokers and contribute to reductions in contemporary cigarette tax responsiveness.
Keywords: I12; I18; H71; H75; 330; prenatal smoking; cigarette taxes; long-term; early-life influences human capital